Aberrant gata-3 expression in human pancreatic cancer - Gulbinas, Antanas; Berberat, Pascal O.; Dambrauskas, Zilvinas; Giese, Thomas; Giese, Nathalia; Autschbach, Frank; Kleeff, Jörg H.; Meuer, Stefan; Büchler, Markus W.; Friess, Helmut (Journal of histochemistry & cytochemistry, 2006)
Gata-3 has been shown to specifically alter its expression patterns in different types of cancers. Recent evidence suggests that an interference of Gata-3 exists in the TGF-beta signaling pathway. To determine the role of Gata-3 in pancreatic cancer, pancreatic cancer samples were analyzed in comparison to normal pancreatic tissues. Furthermore, four different pancreatic cancer cell lines with different alterations of the TGF-beta pathway were studied. To evaluate if a potential relationship with TGF-beta signaling pathway exists, we correlated mRNA expression levels with the expression of TGF-betas, TGF-beta receptors, and Smad-3. Finally, we analyzed the influence of TGF-beta on Gata-3 expression in vitro. All pancreatic cancer samples demonstrated a marked overexpression of Gata-3 mRNA and protein. Immunohistochemical staining revealed strong and persistent cytoplasmic Gata-3 immunoreactivity in cancer cells. In an electrophoretic mobility shift assay, a disturbed nuclear translocation was confirmed. The expression of Gata-3 showed a significant correlation with the expression of TGF-betas, TGF-beta receptors, and Smad-3. TGF-beta responsive cell lines showed a downregulation of Gata-3 mRNA upon TGF-beta exposure, whereas in TGF-beta-unresponsive cell lines, Gata-3 mRNA expression persisted at high levels. Furthermore, strong specific upregulation of Gata-3 impaired nuclear translocation and its cooperative action with the TGF-beta pathway, suggesting that Gata-3 plays a central role in human pancreatic cancer.
Gesehen am 09.06.2021